Clinical-pharmacological medication reviews for insurants of a German statutory health insurance fund (Kaufmännische Krankenkasse (KKH)): a 5-year retrospective analysis (2019–2023) - Johannes Heck; Dirk O. Stichtenoth; Lutz Herbarth; Christoph Schröder; Ruxandra Sabau; Thorben Pape; Sebastian Schröder; Benjamin Krichevsky; Martin Schulze Westhoff; Martin Klietz; Stephan Greten; Patrick-Pascal Strunz; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
This study sought to evaluate the characteristics of clinical-pharmacological (CP) medication reviews conducted by the Institute for Clinical Pharmacology of Hannover Medical School for older, multimorbid, polymedicated insurants of the German statutory health insurance fund Kaufmännische Krankenkasse (KKH). Special emphasis was put on potential sex-specific differences between female and male insurants, prescriptions of potentially inappropriate medications for older individuals (PIMs), and potentially inappropriate duplicate prescriptions (PIDPs). Medication reviews conducted for KKH insurants between 2019 and 2023 ( n = 334) were analyzed retrospectively. Clinical trial number is not applicable. The median age of KKH insurants (58.1% female) was 74 years (first quartile (Q1): 68; third quartile (Q3): 80). Insurants displayed a median of 7 diseases (Q1: 5; Q3: 9) and took a median of 13 drugs (Q1: 11; Q3: 16). A median of 4 CP recommendations was issued per medication review (Q1: 3; Q3: 5). The number of CP recommendations was significantly higher for female compared to male insurants (median of 4 (Q1: 3; Q3: 6) vs. median of 3 recommendations (Q1: 2; Q3: 4); p < 0.001), while the number of drugs was identical and the number of diagnoses was higher for female insurants. The most frequently prescribed PIMs were tricyclic antidepressants, benzodiazepines, and Z-drugs. At least one PIDP was detected in 16.5% of medication reviews. The sex-specific difference in the number of CP recommendations between female and male insurants may point to an unmet pharmacotherapeutic need in older women. PIM prescriptions and PIDPs were relevant topics of CP recommendations, suggesting possibilities for pharmacotherapeutic optimization in older, multimorbid, polymedicated patients.